Analysis of the potential for increasing water retention in road pavements on public roads in cities: a case study based on the Old Town of Płock - Gryszpanowicz, Piotr; Prałat, Karol; Lisicka, Aneta (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The contemporary development of cities necessitates the implementation of modern systems, particularly with regard to the drainage of rainwater and melted snow from road surfaces. Due to the prevalent use of paved surfaces in urban areas, it is crucial to explore solutions that facilitate water retention at the point of occurrence. A key element is the use of biologically active surfaces. When designing specific solutions, it is vital to first review the current water and road regulations. An analysis based on these regulations was conducted to investigate the potential for increasing water retention in pedestrian buffer lanes in the Old Town area of Płock.